Attitudes towards faith-based schooling amongst Roman Catholics in Britain - Clements, Ben (British journal of religious education, 2018)
Separate Catholic schooling in Britain has historically been a key mechanism for the religious socialisation of children within the denomination and for the transmission of communal identity and heritage. Catholic schools currently comprise around a tenth of all state schools in England and nearly all ‘denominational' schools in Scotland. This study analyses Catholics' attitudes towards publicly funded faith schools for different religious groups using a nationally representative survey of adult Catholics in Britain. It assesses the impact of social characteristics, religious behaving and believing, and moral attitudes. Catholics' religious orthodoxy is consistently related to support for state-funding of faith schools, irrespective of the religious group in question, providing some support for the ‘solidarity of the religious' perspective. The effects for moral attitudes are less consistent, with socially conservative views associated with support for faith schools for Catholics and Anglicans, but associated with opposition to faith schools in general and for non-Christian religions.